Proteoma nuclear e micro-RNAs de espermatozoides de bovinos férteis e subférteis - Silva, Ricardo Tomaz da (2018)
SUMMARY - Understanding the composition and physiology of spermatozoa is important to understand transient or permanent subfertility in bulls. Thus, the objective of this work was to evaluate the nuclear and micro-RNA spermatozoa of fertile and subfertile cattle, in an attempt to identify molecular markers of fertility and subfertility in bulls. For the evaluation of micro- RNAs the RNA-seq methodology was used and for nuclear proteins the advanced mass spectrometry of semen samples from fertile and subfertile bulls was used. A total of 1306 micro-RNAs were identified in the semen samples evaluated. The bta-miR-380-5p, bta-miR- 155, bta-miR-122, bta-miR-30c and bta-miR-34a genes were identified by computational analysis as being differentially expressed in fertile and subfertile bulls, indicating that they can set up possible fertility markers. However, it was clear that there is no single micro-RNA that marks different types and causes of subfertility. As for the nuclear proteins, it was possible to verify that spermatozoa of bull have in the constitution of their protamine chromatin 1 and 2, as well as the histone variations subH2Bv, H2A.J, H2A.2C, H4, H2B.1, H1.2, H2A .Z, H3.1, H3.3C, H3.3C-like, H1.3, H3.3, H3.2. Among nuclear proteins and contaminants from other sperm and seminal plasma compartments, the acyl thioesterase 1 protein (APT-1), nerve growth factor beta (Beta-NGF), seminal plasma protein A3 ( BSP-3), Histone H2A.J, FAM71D protein, 40S-S8 and 60S-L9 ribosomal proteins, the plasma serine protease inhibitor (Protein C inhibitor) (Serpin A5) and the catalytic alpha subunit of the cAMP-dependent protein kinase as having potential to be used as a fertility marker. On the other hand, the ATPase protein of the transitional endoplasmic reticulum, subunit 5 of NADH dehydrogenase (ubiquinone) of subcomplex 1 alpha, beta-9 heat shock protein, ribosomal proteins 60S-L12 and 40S-S7 and acetyl-CoA protein acetyltransferase presented potential to be used as subfertility markers.